Nitrogen and phosphorus dual-doped porous carbon with controllable pore structure and preparation method thereof and negative electrode material
By achieving stereo doping of nitrogen and phosphorus in porous carbon, combining the curing and carbonization process of resin oligomers and compounds, the problems of high cost of doping matrix and unsatisfactory porous structure in the prior art are solved, and the preparation of high-performance porous silicon carbon negative electrode materials is realized, which improves the kinetics and expansion cycle resistance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411509932.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-10-28
AI Technical Summary
In the prior art, the raw materials of nitrogen-phosphorus doped doped doped matrix are costly and have limited mass production capacity. It is difficult to achieve ideal results in pore structure and doping effect of conventional materials, and cannot meet the requirements of lithium-ion batteries in terms of kinetics and anti-expansion cycles.
Through the polymerization and cross-linking curing of resin oligomers, phosphorus-containing compounds and nitrogen-containing compounds, the double doping of nitrogen-phosphorus bulk is achieved, and combined with the surface doping process, the nitrogen-phosphorus three-dimensional doped porous carbon is formed, which not only improves the overall performance of porous carbon, but also regulates the pore structure characteristics.
The three-dimensional doping of nitrogen and phosphorus double-doped elements on the inside and surface of porous carbon is achieved, the conductivity and stability of porous carbon is improved, the lithium ion diffusion performance is enhanced, and the kinetic performance and specific capacity of porous silicon carbon anode material is improved.
Smart Images

Figure CN119018893B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a nitrogen-phosphorus dual-doped porous carbon with a controllable pore structure, a preparation method thereof, and a negative electrode material. Background Art
[0002] As the main component matrix of porous silicon carbon, the high rate performance of porous carbon itself can effectively improve the kinetic performance of the finished product. Therefore, by doping other substances that are beneficial to improving the conductivity and thus the kinetic performance, the overall kinetic performance of the battery can be effectively improved, which is an important research goal to solve the current lithium-ion battery application in the power field. Porous silicon-carbon negative electrode material uses porous carbon as a carrier, and deposits the silicon source into the pores of porous carbon under a certain temperature and pressure to form a silicon-carbon negative electrode material. Porous carbon is mainly composed of micropores and mesopores. The deposited silicon is separated by the micropores and mesopores of porous carbon. There is no large particle silicon, and the expansion stress is small. At the same time, the porous structure of porous carbon provides space for the expansion of silicon. Therefore, porous silicon-carbon negative electrode material has the advantages of good anti-expansion and long cycle performance, and is unanimously regarded as one of the most promising battery negative electrode materials in the future. Porous carbon is the core material of porous silicon-carbon negative electrode material. The morphology, composition, and pore structure of porous carbon have a significant impact on the product performance of porous silicon-carbon negative electrode material.
[0003] Undoped porous carbon has poor kinetics in depositing porous silicon carbon. Due to the limited rate of lithium ion extraction, the application of porous silicon carbon in the power market is limited. Therefore, the existing porous carbon is also improved by element doping. The existing technology for preparing phosphorus and nitrogen doped porous carbon basically uses a nitrogen / phosphorus matrix. After carbonization, it is further expanded by chemical or physical methods to achieve the desired pore structure. However, there are still shortcomings in the preparation method of phosphorus and nitrogen doped porous carbon in the prior art.
[0004] Existing patent CN109824048B: Preparation of a nitrogen-phosphorus co-doped carbon-based material and its application in supercapacitors, discloses a method for preparing a nitrogen-phosphorus co-doped carbon-based material and its application in supercapacitors, which combines phytic acid molecules with amino acid small molecules through hydrogen bonding forces, and does not require the use of complex methods such as potassium hydroxide activation and zinc chloride activation for pore expansion treatment. After simple high-temperature roasting, a nitrogen-phosphorus co-doped carbon-based material with a large specific surface area is obtained, and the preparation process is simple and green. Its disadvantages are: the activated material is flaky, the pores created are mostly macropores and mesopores, the strength and pore structure are not suitable for the field of gas phase silicon carbon, and the batch stability of biomass raw materials is poor, and the product quality consistency and stability cannot be guaranteed.
[0005] The existing paper "Study on the Structure and Properties of Phosphorus- and Nitrogen-Containing Phenolic Resin-Based Carbonized Materials" discloses that a phosphorus- and nitrogen-containing phenolic resin (NP-PF) was synthesized using phosphorus-containing monomers, melamine, phenol, and formaldehyde as raw materials. NP-PF was cured, and the carbonization process of the cured material and the structure of the carbonized material were investigated by infrared, thermogravimetric analysis of specific surface area, and electron microscopy analysis. The results show that the surface of the nitrogen-containing phenolic resin carbonized material is rough and loose, with rich pore structure and a specific surface area of 971.25 m 2 / g. With the introduction of phosphorus-containing components, the pores on the surface of NP-PF carbonized products become fewer and the main structure is denser. Due to the combined effect of phosphorus and nitrogen, the residual carbon rate of NP-PF solidified products increased to 57.5%, which is similar to the residual carbon rate of PF solidified products. NP-PF can be used as a precursor of high-strength carbon. Its defects are mainly reflected in the fact that it adopts organic small molecule synthesis, which involves large chemical mass production issues in mass production and has a high threshold for industrialization; secondly, it adopts direct pyrolysis to form pores, and the pores formed are mostly mesopores, and it is difficult to avoid the appearance of large pores, and the consistency and stability of the pore structure cannot be guaranteed; thirdly, the specific surface area of the porous carbon obtained by direct pyrolysis to form pores is low, and porous carbon with large specific surface area and large pore volume cannot be obtained.
[0006] The existing paper "Nitrogen and phosphorus Co-doped porous carbon_ Dopant, synthesis, performance enhancement mechanism and versatile applications" discloses that two main substrates are used, one is a biological precursor containing phosphorus and nitrogen elements, such as protein, etc. The defects of biomass precursors are as mentioned above, and the consistency, stability and purity cannot be guaranteed; the other is a non-biomass precursor, mainly a resin precursor, one part of which is a precursor containing phosphorus and nitrogen elements, which is in situ pyrolyzed to form co-doped porous carbon, and the other part is post-treated by small molecules containing phosphorus and nitrogen elements, and phosphorus and nitrogen elements are doped on the surface. The first part involves pyrolysis of small molecules, and the strength and yield cannot meet the mass production requirements. The latter part uses different treating agents (containing single element components (N, P), or containing double element components (N / P)), which can only be surface doped, and body-doped porous carbon cannot be obtained, which is not conducive to the use of doped elements.
[0007] In the prior art, the doping matrix with good doping at this stage is conductive polymers such as polyaniline, polypyrrole, and polythiophene, which can be doped with nitrogen and sulfur elements. At the same time, the conjugated system is conducive to further increasing the conductive performance, but the price of conjugated polymer materials is high and the mass production capacity is limited, which limits its further mass production. At the same time, it is difficult to achieve a more ideal result in the doping effect and porous carbon pore structure of conventional materials. Especially for porous silicon-carbon negative electrode materials, whether it is direct pyrolysis pore formation or physical activation pore formation, its pore volume and pore size are too low to meet the kinetic requirements, and the anti-expansion cycle effect cannot meet the design requirements.
[0008] Therefore, the existing technology needs to be improved. Summary of the invention
[0009] In the prior art, the cost of the doping matrix raw materials for nitrogen and phosphorus doping is high and the mass production capacity is limited. It is difficult to achieve a relatively ideal result in the doping effect and porous carbon pore structure by using conventional materials for doping porous carbon. Therefore, it is necessary to provide a nitrogen and phosphorus dual-doped porous carbon with controllable pore structure and its preparation method and negative electrode material to solve the above problems.
[0010] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing nitrogen-phosphorus dual-doped porous carbon with controllable pore structure, which comprises the following specific steps:
[0011] S1, curing resin: providing 10-80 parts of a resin oligomer, 1-50 parts of a phosphorus-containing compound and 1-50 parts of a nitrogen-containing compound for polymerization, cross-linking and curing to obtain a curing resin;
[0012] S2, carbonization: carbonizing the cured resin of S1 at a temperature of 300-800°C in a nitrogen or argon atmosphere to obtain a carbonized resin;
[0013] S3, activation: activating the carbonized resin of S2 to obtain a porous structure material;
[0014] S4, washing the porous structure material in S3 with water and acid and alkali, and then drying;
[0015] S5, surface doping: mixing the dried porous structure material with nitrogen and phosphorus surface dopants, and performing surface doping at high temperature to obtain a surface dual-doped porous carbon;
[0016] S6. After ultrasonic washing, alkali washing, acid washing and rinsing of the porous carbon in S5, the porous carbon is dried and broken up for classification to obtain crushed nitrogen-phosphorus dual-doped porous carbon with controllable pore structure.
[0017] In one implementation, in S1, the resin oligomer is a resin containing a catalyst, the catalyst includes any one or more of urotropine, Na2CO3, NaHCO3 and NaOH, and the resin is any one of phenolic resin, melamine resin and urea-formaldehyde resin; the phosphorus-containing compound includes any one or more of phosphoric acid, phytic acid, hexachlorotriphosphazene, monophenyl phosphate, diphenyl phosphate, and triphenyl phosphate; the nitrogen-containing compound includes any one or more of nitric acid, cyanamide, dicyandiamide, melamine, urea, thiourea and acetonitrile.
[0018] In one implementation, in S1, the mass fraction of the resin oligomer is 10-80 parts, the mass fraction of the phosphorus-containing compound is 1-50 parts, and the mass fraction of the nitrogen-containing compound is 1-50 parts.
[0019] In one implementation, in S3, the specific steps include: the carbonization specific surface area of the carbonized resin is 100m 2 / g or more, it can be directly physically activated by water vapor or CO2; the carbonized specific surface area of the carbonized resin is 100m 2 / g or less, pre-activation is required. By adding an alkali-carbon ratio of (0.3~1):1, pores are formed once, and the pore specific surface area is below 1000. Then, physical activation is performed for secondary pore expansion to obtain a porous structure material.
[0020] In one implementation, in S3, the specific surface area of the porous structure material obtained is 500-3500 m 2 / g, pore volume is 0.2~2.0ml / g, average pore diameter is 1.0~5.5nm, and microporosity is 5~100%.
[0021] In one implementation, in S5, the nitrogen-phosphorus surface dopant includes any one of ammonium pyrophosphate, ammonium polyphosphate, ammonium phosphate, ammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphite, ammonium hypophosphite, phosphoric acid / nitric acid mixed acid and NH3 / PH3 mixed gas.
[0022] In one implementation, in S5, the surface doping temperature is 300-700° C., carried out in a nitrogen / mixed gas atmosphere, and the doping time is 1-5 hours.
[0023] In a second aspect, the present invention further provides a nitrogen-phosphorus dual-doped porous carbon with controllable pore structure, which is prepared by any of the above-mentioned methods for preparing nitrogen-phosphorus dual-doped porous carbon with controllable pore structure.
[0024] In one implementation, the nitrogen-phosphorus dual-doped porous carbon with controllable pore structure has a phosphorus content of 0.3-10% by mass, and a nitrogen content of 0.5-15% by mass.
[0025] In a third aspect, the present invention further provides a negative electrode material, which comprises any of the nitrogen-phosphorus dual-doped porous carbons with controllable pore structures described above.
[0026] Beneficial effect: The preparation method of nitrogen-phosphorus dual-doped porous carbon with controllable pore structure provided by the present invention realizes nitrogen-phosphorus dual-doping through polymerization, cross-linking and curing of resin oligomers, phosphorus-containing compounds and nitrogen-containing compounds, and forms nitrogen-phosphorus stereo-doped porous carbon in combination with surface doping process, so that nitrogen-phosphorus dual-doping elements are simultaneously doped inside and on the surface of the porous carbon, which can simultaneously improve the overall performance and surface characteristics of the porous carbon; at the same time, after carbonization and then activation, a controllable pore structure is formed in the activation process, which can not only obtain doped porous carbon with high value ratio, but also can flexibly design the pore structure, providing a porous silicon-carbon negative electrode material with excellent high-rate performance, thereby improving the conductivity and thus the kinetic performance, which can effectively improve the overall kinetic performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a flow chart of the steps of the method for preparing nitrogen-phosphorus dual-doped porous carbon with controllable pore structure provided by the present invention;
[0028] Figure 2 This is the XPS spectrum of the P structure of the nitrogen and phosphorus dual-doped porous carbon with controllable pore structure obtained in Example 3;
[0029] Figure 3 This is the XPS spectrum of the N structure of the nitrogen and phosphorus dual-doped porous carbon with controllable pore structure obtained in Example 3;
[0030] Figure 4 1 is a schematic diagram of the process steps of the porous carbon GITT test of Examples 1 to 3 and the comparative example;
[0031] Figure 5 It is a diffusion coefficient curve diagram of the GITT test of the porous carbon of Examples 1 to 3 and the comparative example.
[0032] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0034] See also Figure 1 , Figure 1 The present invention provides a method for preparing nitrogen-phosphorus dual-doped porous carbon with controllable pore structure, which comprises the following specific steps:
[0035] S1, curing resin: providing 10-80 parts of a resin oligomer, 1-50 parts of a phosphorus-containing compound and 1-50 parts of a nitrogen-containing compound for polymerization, cross-linking and curing to obtain a curing resin;
[0036] S2, carbonization: carbonizing the cured resin of S1 at a temperature of 300-800°C in a nitrogen or argon atmosphere to obtain a carbonized resin;
[0037] S3, activation: activating the carbonized resin of S2 to obtain a porous structure material;
[0038] S4, washing the porous structure material in S3 with water and acid and alkali, and then drying;
[0039] S5, surface doping: mixing the dried porous structure material with nitrogen and phosphorus surface dopants, and performing surface doping at high temperature to obtain a surface dual-doped porous carbon;
[0040] S6. After ultrasonic washing, alkali washing, acid washing and rinsing of the porous carbon in S5, the porous carbon is dried and broken up for classification to obtain crushed nitrogen-phosphorus dual-doped porous carbon with controllable pore structure.
[0041] Specifically, in S1, the resin oligomer is a resin containing a catalyst, the catalyst includes any one or more of urotropine, Na2CO3, NaHCO3 and NaOH, the resin is any one of phenolic resin, melamine resin and urea-formaldehyde resin; the phosphorus-containing compound includes any one or more of phosphoric acid, phytic acid, hexachlorotriphosphazene, monophenyl phosphate, diphenyl phosphate, triphenyl phosphate; the nitrogen-containing compound includes any one or more of nitric acid, cyanamide, dicyandiamide, melamine, urea, thiourea and acetonitrile. After phosphorus / nitrogen doping, the matrix can improve the affinity for solvents and lithium ions, which is conducive to rapid penetration into the matrix; at the same time, after phosphorus doping, since the phosphorus atom has a larger diameter than the carbon atom, it can expand the atomic gap, which is conducive to the diffusion of lithium ions and improve the diffusion coefficient.
[0042] Further, the mass fraction of the resin oligomer is 10 to 80 parts, the mass fraction of the phosphorus-containing compound is 1 to 50 parts, and the mass fraction of the nitrogen-containing compound is 1 to 50 parts. The present invention adopts commonly used resin raw materials, and through formula design and process improvement, it is possible to ensure the proportion and structure of doping elements without using high-priced raw materials, comprehensively improve the quality-price ratio of doped porous carbon, and is conducive to further industrialization. Among them, the raw materials provided by the present invention, such as phenolic resin, melamine resin, urea-formaldehyde resin, melamine, phosphoric acid, tricresyl phosphate, diammonium phosphate, monoammonium phosphate, etc., are commonly used chemical raw materials, and the price is similar to that of resin porous carbon, so it can be effectively doped into doped porous carbon, which has little effect on the price of subsequent mass-produced products, can be directly mass-produced, and has high economic value.
[0043] Specifically, in S3, the specific steps include: the carbonization specific surface area of the carbonized resin is 100m 2 / g or more, it can be directly physically activated by water vapor or CO2; the carbonized specific surface area of the carbonized resin is 100m 2 / g or less, it needs to be pre-activated, by adding (0.3~1) : 1 alkali carbon ratio, to make a hole, the pore specific surface area is less than 1000, and then physical activation secondary pore expansion is performed to obtain a porous structure material. Through this activation step, the porous carbon material has a large adsorption capacity and excellent mass transfer performance
[0044] Specifically, in S3, the specific surface area of the porous structure material obtained is 500~3500m 2 / g, pore volume of 0.2~2.0ml / g, average pore size of 1.0~5.5nm, and microporosity of 5~100%. Through specific curing, carbonization and activation steps, combined with the use of additives (resin oligomers, phosphorus-containing compounds and nitrogen-containing compounds), the pore structure characteristics of porous carbon, including specific surface area, pore volume and average pore size, can be precisely controlled. This precise control enables porous carbon materials to exhibit excellent performance in different application scenarios.
[0045] Specifically, in S5, the nitrogen-phosphorus surface dopant includes any one of ammonium pyrophosphate, ammonium polyphosphate, ammonium phosphate, ammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphite, ammonium hypophosphite, phosphoric acid / nitric acid mixed acid and NH3 / PH3 mixed gas. Further, the surface doping temperature is 300~700℃, carried out in a nitrogen / mixed gas atmosphere, and the doping time is 1~5h. The dual doping of nitrogen and phosphorus not only improves the chemical activity of porous carbon, but also enhances its conductivity and stability. Nitrogen doping improves the conductivity and surface activity of the material, while phosphorus doping improves the thermal stability and antioxidant properties of the material. In this step, combined with surface doping, the distribution and doping concentration of the dopant inside and on the surface of the porous carbon material can be effectively controlled, making the performance of the material more excellent and uniform. The prepared nitrogen-phosphorus dual-doped pore structure controllable porous carbon material has excellent electrochemical properties, is particularly suitable for negative electrode materials of high-performance batteries, and exhibits high capacity and long life.
[0046] In addition, during the preparation process, inert gases such as nitrogen or argon are used for carbonization and doping, which reduces the emission of harmful gases and meets the requirements of green chemistry.
[0047] In a second aspect, the present invention further provides a nitrogen-phosphorus dual-doped porous carbon with a controllable pore structure, which is prepared by any of the above-mentioned methods for preparing nitrogen-phosphorus dual-doped porous carbon with a controllable pore structure. Specifically, the nitrogen-phosphorus dual-doped porous carbon with a controllable pore structure has a phosphorus content of 0.3-10% by mass and a nitrogen content of 0.5-15% by mass.
[0048] In a third aspect, the present invention further provides a negative electrode material, which comprises any of the nitrogen-phosphorus dual-doped porous carbons with controllable pore structures described above.
[0049] The present invention also describes the present technology in detail through the following examples and comparative examples.
[0050] Embodiment 1:
[0051] Phenolic resin prepolymer (molecular weight of about 200) mixed with hexamethylenetetramine was mixed with triphenyl phosphate (TCP) in a ratio of 1:1, and the temperature was gradually increased until the viscosity increased slightly, 1% CMC (carboxymethyl cellulose) was added for thickening, and finally appropriate melamine was added to make the mass ratio of phenolic resin prepolymer: TCP: melamine 1:1:1. After thorough mixing, further curing was carried out under stirring until melamine was no longer precipitated and layered, and then poured into a Teflon-coated tray for post-curing, and the temperature was gradually increased to 150°C and cured for 2 hours;
[0052] The solidified material is crushed into small pieces of 2-3 mm by a jaw crusher, and then put into a box-type atmosphere furnace or a rotary kiln for carbonization under a nitrogen atmosphere at a carbonization temperature of 500°C for a carbonization time of 2 h to obtain a carbonized material;
[0053] The carbonized material is directly physically activated in a rotary kiln at 800°C in an atmosphere of N2:CO2=1:1 for 6 hours;
[0054] After ultrasonic washing of the activated carbonized material, the full pore structure was tested and found to be 1513m 2 / g, 0.7ml / g, pore size 1.85nm;
[0055] The doped porous carbon was post-passivated at 500°C in a mixed atmosphere of NH3 / PH3 for 2 h;
[0056] The passivation material is washed and dried, then crushed and classified to obtain a nitrogen-phosphorus dual-doped porous carbon product with a controllable pore structure and a particle size distribution that meets the requirements.
[0057] The elemental analysis of the heat-treated nitrogen-phosphorus dual-doped porous carbon with controllable pore structure showed that the nitrogen content was 5.3%, the phosphorus content was 1.1%, and the oxygen content was 0.87%.
[0058] Embodiment 2:
[0059] Mix the phenolic resin prepolymer (molecular weight of about 100) catalyzed by Na2CO3 with monophenyl phosphate in a ratio of 1:1, and gradually heat and mix until the viscosity increases slightly, add 1% polyvinyl alcohol 2000 for thickening, and finally add appropriate melamine to make the mass ratio of urea-formaldehyde resin prepolymer: monophenyl phosphate: melamine 1:1:1. After thorough mixing, further cure while stirring until the melamine does not precipitate and stratify, then pour into a Teflon-coated tray for post-curing, gradually heat to 150°C and cure for 2 hours;
[0060] The solidified material is crushed into small pieces of 2-3 mm by a jaw crusher, and then put into a box-type atmosphere furnace or a rotary kiln for carbonization under a nitrogen atmosphere at a carbonization temperature of 500°C for a carbonization time of 2 h to obtain a carbonized material;
[0061] The carbonized material is directly physically activated in a rotary kiln at 800°C in an atmosphere of N2:H2O=1:1 for 4 hours;
[0062] After the activated carbonized material was ultrasonically washed, the full pore structure was tested and the pore structure was 1746m 2 / g, 0.8ml / g, pore size 1.83nm;
[0063] The above-mentioned doped porous carbon was mixed evenly with ammonium monohydrogen phosphate in a ratio of 1:3, and post-passivated at 700°C for 2h;
[0064] The passivation material is washed and dried, and then crushed and classified to obtain a nitrogen-phosphorus dual-doped porous carbon product with a controllable pore structure having a particle size distribution that meets the requirements;
[0065] The elemental analysis of the heat-treated nitrogen-phosphorus dual-doped porous carbon with controllable pore structure showed that the nitrogen content was 4.5%, the phosphorus content was 0.9%, and the oxygen content was 0.73%.
[0066] Embodiment 3:
[0067] The phenolic resin prepolymer (molecular weight of about 1000) catalyzed by NaHCO3 was mixed with diphenyl phosphate in a ratio of 1:1, and the temperature was gradually increased until the viscosity increased slightly, 0.6% CMC was added for thickening, and finally appropriate urea was added to make the mass ratio of phenolic resin prepolymer: diphenyl phosphate: urea 1:1:1. After thorough mixing, further curing was carried out under stirring until melamine was no longer precipitated and layered, and then poured into a Teflon-coated tray for post-curing, and the temperature was gradually increased to 150°C for curing for 2 hours.
[0068] The solidified material is crushed into small pieces of 2-3 mm by a jaw crusher, and then put into a box-type atmosphere furnace or a rotary kiln for carbonization under a nitrogen atmosphere at a carbonization temperature of 500°C for a carbonization time of 2 h to obtain a carbonized material;
[0069] The carbonized material was first mixed with KOH (1:0.3) and ground, and activated at 750°C for 2h;
[0070] The pore structure obtained by washing is 324m 2 / g, pore volume 0.12ml / g, primary porous carbon with pore diameter 1.48nm;
[0071] The activation was carried out in a rotary kiln at 800°C in an atmosphere of N2:CO2=1:1 for 3h;
[0072] After ultrasonic washing of the activated carbonized material, the full pore structure was tested and found to be 1913m 2 / g, 0.9ml / g, pore size 1.88nm;
[0073] The doped porous carbon and ammonium dihydrogen phosphate were mixed evenly in a ratio of 1:4, and post-passivated at 600°C for 2h;
[0074] The passivation material is washed and dried, and then crushed and classified to obtain a nitrogen-phosphorus dual-doped porous carbon product with a controllable pore structure having a particle size distribution that meets the requirements;
[0075] The heat-treated nitrogen-phosphorus dual-doped porous carbon with controlled pore structure was subjected to elemental analysis, and its nitrogen content was 3.2%, phosphorus content was 1.5%, and oxygen content was 0.75%. The structure of the nitrogen / phosphorus doped carbon was tested by XPS (X-ray photoelectron spectroscopy). Figure 2 and Figure 3 Among them, the horizontal axis is binding energy (Binding Energy), and the vertical axis is intensity (Intensity).
[0076] The parameters of the porous carbon provided by Examples 1 to 3 and the comparative example are shown in Table 1.
[0077] Table 1, Parameter statistics of porous carbon provided in Examples 1 to 3 and Comparative Examples:
[0078] .
[0079] The above four nitrogen-phosphorus dual-doped porous carbons with controllable pore structures were used as the main negative electrode materials, mixed with a conductive agent (Super-P) and a binder LA132 (15wt%) in a mass ratio of 70:20:10 to prepare a slurry, which was coated on a copper foil and dried in a vacuum oven to prepare a negative electrode sheet. A 1 mol / L LiPF6 electrolyte (the volume ratio of ethylene carbonate and diethyl carbonate in the solvent = 1:1) was used, a polypropylene microporous membrane was used as a separator, and a lithium sheet was used as a negative electrode to assemble a button cell. The electrochemical performance was tested on a blue battery test system. Figure 4 The GITT process flow chart of the work step test is shown in the figure. The test results are as follows Figure 5 As shown. Among them, Figure 5 The abscissa Potential shows the potential measured at different current pulses and resting stages in the GITT measurement; the ordinate logD shows the logarithmic value of the diffusion coefficient measured by the GITT measurement.
[0080] pass Figure 5The results show that the lithium ion diffusion coefficient of the porous carbon with controllable pore structure of nitrogen and phosphorus dual doping obtained in Examples 1 to 3 is increased by 3.98 times through pore structure design and nitrogen and phosphorus dual doping, which proves that the solution of the present invention is feasible.
[0081] In summary, the preparation method of the nitrogen-phosphorus dual-doped porous carbon with controllable pore structure provided by the present invention realizes nitrogen-phosphorus dual-doping through polymerization and cross-linking curing of resin oligomers, phosphorus-containing compounds and nitrogen-containing compounds, and combines the surface doping process to form nitrogen-phosphorus stereo-doped porous carbon, so that the nitrogen-phosphorus dual-doping elements are simultaneously doped inside and on the surface of the porous carbon, which can effectively improve the affinity and diffusion performance of the porous carbon skeleton for lithium ions, help to improve the performance of porous silicon carbon in high-rate charge and discharge of lithium-ion batteries, help to further improve the specific capacity and charge and discharge effect of lithium-ion batteries, and can further promote the upgrading of electric vehicles. The selected materials are all existing chemical and biomedical raw materials produced in large quantities, which are cheap and easy to obtain. The designed dual-doped porous carbon has the advantages of high strength, good performance, and designable structure. It can also ensure that the price is consistent with ordinary porous carbon, which is conducive to the promotion and mass production of products and has huge economic benefits. At the same time, after carbonization, activation is performed, and the pore structure formed in the activation process is controllable, which can not only obtain doped porous carbon with high value ratio, but also flexibly design the pore structure, provide a porous silicon-carbon negative electrode material with excellent high rate performance, thereby improving the conductivity and thus the kinetic performance, and can effectively improve the overall kinetic performance of the battery. The present invention provides a high-performance, structure-controllable, high-purity and highly adaptable nitrogen-phosphorus dual-doped porous carbon material, which has broad application prospects in the fields of energy storage, catalysis and environmental protection.
[0082] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing nitrogen-phosphorus dual-doped porous carbon with controllable pore structure, characterized in that: The specific steps include: S1, curing resin: providing 10-80 parts by mass of a resin oligomer, 1-50 parts by mass of a phosphorus-containing compound and 1-50 parts by mass of a nitrogen-containing compound for polymerization, cross-linking and curing to obtain a curing resin; S2, carbonization: carbonizing the cured resin of S1 at a temperature of 300-800°C in a nitrogen or argon atmosphere to obtain a carbonized resin; S3, activation: activating the carbonized resin of S2 to obtain a porous structure material; S4, washing the porous structure material in S3 with water and acid and alkali, and then drying; S5, surface doping: mixing the dried porous structure material with nitrogen and phosphorus surface dopants, and performing surface doping at a temperature of 300-700°C to obtain a surface dual-doped porous carbon; S6. After ultrasonic washing, alkali washing, acid washing and rinsing of the porous carbon in S5, the porous carbon is dried and broken up for classification to obtain crushed nitrogen-phosphorus dual-doped porous carbon with controllable pore structure.
2. The method for preparing nitrogen-phosphorus dual-doped porous carbon with controllable pore structure according to claim 1, characterized in that: In S1, the resin oligomer is a resin containing a catalyst, the catalyst includes any one or more of urotropine, Na2CO3, NaHCO3 and NaOH, and the resin is any one of phenolic resin, melamine resin and urea-formaldehyde resin; the phosphorus-containing compound includes any one or more of phosphoric acid, phytic acid, hexachlorotriphosphazene, monophenyl phosphate, diphenyl phosphate, and triphenyl phosphate; the nitrogen-containing compound includes any one or more of nitric acid, cyanamide, dicyandiamide, melamine, urea, thiourea and acetonitrile.
3. The method for preparing nitrogen-phosphorus dual-doped porous carbon with controllable pore structure according to claim 1, characterized in that: In S3, the specific steps include: the carbonization specific surface area of the carbonized resin is 100m 2 / g or more, it can be directly physically activated by water vapor or CO2; the carbonized specific surface area of the carbonized resin is 100m 2 / g or less, pre-activation is required. By adding alkali with an alkali-to-carbon ratio of (0.3~1):1, pores are formed once, and the pore specific surface area is below 1000. Then, physical activation is performed for secondary pore expansion to obtain a porous structure material.
4. The method for preparing nitrogen-phosphorus dual-doped porous carbon with controllable pore structure according to claim 3, characterized in that: In S3, the specific surface area of the porous structure material obtained is 500~3500m 2 / g, pore volume is 0.2~2.0ml / g, average pore diameter is 1.0~5.5nm, and microporosity is 5~100%.
5. The method for preparing nitrogen-phosphorus dual-doped porous carbon with controllable pore structure according to claim 1, characterized in that: In S5, the nitrogen-phosphorus surface dopant includes any one of ammonium pyrophosphate, ammonium polyphosphate, ammonium phosphate, ammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphite, ammonium hypophosphite, phosphoric acid / nitric acid mixed acid and NH3 / PH3 mixed gas.
6. The method for preparing nitrogen-phosphorus dual-doped porous carbon with controllable pore structure according to claim 5, characterized in that: In S5, the process is carried out in an atmosphere of NH3 / PH3 mixed gas, and the doping time is 1 to 5 hours.
7. A nitrogen-phosphorus dual-doped porous carbon with controllable pore structure, characterized in that it is prepared by the preparation method of nitrogen-phosphorus dual-doped porous carbon with controllable pore structure according to any one of claims 1 to 6.
8. The nitrogen-phosphorus dual-doped porous carbon with controllable pore structure according to claim 7, characterized in that: The mass fraction of phosphorus content in the nitrogen-phosphorus dual-doped porous carbon with controllable pore structure is 0.3-10%, and the mass fraction of nitrogen content is 0.5-15%.
9. A negative electrode material, characterized in that: It comprises the nitrogen and phosphorus dual-doped porous carbon with controllable pore structure as described in claim 7 or 8.
Citation Information
Patent Citations
Preparation of a nitrogen-phosphorus co-doped carbon-based material and its application in supercapacitors
CN109824048B
Nitrogen-manganese co-doped hierarchical porous carbon material preparation method
CN106430146A
Activated carbon material, preparation method thereof and supercapacitor
CN113903598A